QoS guaranteed multi-user and multi-traffic scheduling algorithm for IEEE 802.16 network - BAI Bo1; CAO Zhi-gang1; CHEN Wei1; I Chih-lin2 (Tongxin xuebao)
Based on IEEE 802.16 protocol,the QoS guaranteed multi-user and multi-traffic resourle allocat scheduling problem were studiedin broadband wireless access network.Tirst,the cross-layer analysis model was given by TDM-OFDMA based on multi-access queuing scheduling system.Then,based on convex optimization method,the minimum residual integrated workload algorithm was proposed.It can be shown that the algorithm has guaranteed the QoS requirements asymptotically when the QoS parameters of arriving traffic are in the stability region of this algorithm;meanwhile,the residual integrated workload of the scheduling system has been minimized.It is also verified by the numerical results of simulation experiments that the algorithm can guarantee the QoS requirements of four types of services actually.